A Critical Analysis on the Concept of "Philhellen" on Parthian Coins - Esmaeil Sangari; Alireza Karbasi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The approach of contemporary western historians on the term of “Philhellen” on the coins of the Parthian kings has two types of interpretations. Some consider the superiority of Greek culture to Persian culture in Parthian period, and it is considered as a kind of unconditional and cultural surrender to Greek culture. Some other viewpoints, most of which are based on the later Western historians’ viewpoints, are that this term was used as a "political trick" by Parthian kings in order to control the Greek settlers in their territory. In this view, the use of the term on Parthian coins has not meant the unconditional surrender of Iranian culture to Greek culture, and its whole meaning has not been summed up in political goals, necessarily. What was created during Helenism and especially under the influence of stoic thoughts and its Iranian roots of thought was a global approach to the concept of humanity, which was fundamentally different from that of the Greeks before. This issue was compatible with Iranians’ perception from the global society that was rooted in Zoroastrian thoughts in Achaemenid period. Thus, the Parthian kings, using this interpretation, in fact, admire a kind of Greek culture that has a global and non-transcendental attitude towards human society and so that paved the way for its absorption in Iranian culture. This paper aims to provide a moderate judgment with a cultural-sociological approach by showing the cultural difference between Greeks and Iranians in the Hellenistic period and before that, using literary and archaeological evidence, with a descriptive-analytical method.